2021
DOI: 10.1093/tas/txab046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varying sources of Cu, Zn, and Mn on mineral status and preferential intake of salt-based supplements by beef cows and calves and rainfall-induced metal loss

Abstract: Three studies were completed to evaluate the effects of Cu, Zn, and Mn source on preferential intake, trace mineral status and rainfall-induced metal loss of salt-based mineral supplements. Mineral supplements were formulated to contain 2,500, 5,500, and 4,000 mg/kg of Cu, Zn, and Mn, respectively. Supplements differed only by source of Cu, Zn, and Mn, which were hydroxychloride, organic, or sulfate sources. In Exp. 1, the 3 formulations were offered simultaneously for 18 wk to pre-weaned beef calves (4 pastur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…This theory was further examined in a later study [102] where beef calves were shown to preferentially consume creep feed supplements fortified with hydroxychloride vs. sulfate or organic sources of Cu, Zn, and Mn. Further studies support this preferential intake behavior in other supplementation strategies common for grazing beef cattle, such as cooked molasses tubs [103] and free-choice, salt-based supplements [104]. In the latter study [104], trace mineral solubility was assessed in a rainfall simulation model.…”
Section: Hydroxychloride Trace Mineralsmentioning
confidence: 92%
“…This theory was further examined in a later study [102] where beef calves were shown to preferentially consume creep feed supplements fortified with hydroxychloride vs. sulfate or organic sources of Cu, Zn, and Mn. Further studies support this preferential intake behavior in other supplementation strategies common for grazing beef cattle, such as cooked molasses tubs [103] and free-choice, salt-based supplements [104]. In the latter study [104], trace mineral solubility was assessed in a rainfall simulation model.…”
Section: Hydroxychloride Trace Mineralsmentioning
confidence: 92%